2009
DOI: 10.1358/mf.2009.31.5.1380489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aspirin treatment in streptozotocin-induced type 2 diabetic rats

Abstract: In the present study, we aimed to investigate the role of aspirin in preventing type 2 diabetes in rats. At 5 days old, rat pups were divided into four groups. Group I pups received citrate buffer solution and served as control; group II was treated only with streptozotocin (80 mg/kg i.p.) and served as the diabetic control; groups III and IV were treated with aspirin (10 mg/kg/day p.o.) for 1 and 2 months, respectively, after streptozotocin treatment and served as treated groups. During weeks 8 and 10, blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…According to Coe et al (36), aspirin therapy reduces diabetic mouse nonfasting blood glucose levels, has an ability to stimulate insulin and glucagon secretion and to provide improved glucose tolerance in control animals. However, according to Martha et al (37) aspirin pretreatment (10 mg/kg/day for one and two months) most obviously protect the pancreas from STZ-damage and regulates glucose levels in diabetic rats. Moreover, they found increased insulin sensitivity and reduced insulin resistance, which may indicate of involvement of IGF-1 in an insulin like pathway.…”
Section: Table 4 Statistical and Percentage Analyses Of Glycogen Cont...mentioning
confidence: 99%
“…According to Coe et al (36), aspirin therapy reduces diabetic mouse nonfasting blood glucose levels, has an ability to stimulate insulin and glucagon secretion and to provide improved glucose tolerance in control animals. However, according to Martha et al (37) aspirin pretreatment (10 mg/kg/day for one and two months) most obviously protect the pancreas from STZ-damage and regulates glucose levels in diabetic rats. Moreover, they found increased insulin sensitivity and reduced insulin resistance, which may indicate of involvement of IGF-1 in an insulin like pathway.…”
Section: Table 4 Statistical and Percentage Analyses Of Glycogen Cont...mentioning
confidence: 99%
“…Lin and his coworkers [49] treated Sprague-Dawley (SD) rats with high fat diet for a 10-week with low dose of aspirin (5 mg/kg Bw) found that lowdose aspirin ameliorated hyperinsulinemia and hyperlipidemia, recovered activated partial thromboplastin and prothrombin time, prevent adhesion molecules expression and chemokine formation. Rat pups (neonates) that were treated with 10 mg/kg BW aspirin for one month after streptozotocin administration showed significant reduction in blood glucose levels and insulin resistance and significant improvement in insulin levels and insulin sensitivity [50].…”
Section: Antidiabetic Effect Of Low Dose Aspirinmentioning
confidence: 99%